Strategi Komunikasi Persuasif Guru dalam Meningkatkan Motivasi Belajar Siswa : (Studi Kasus SD Islam Sinar Cendekia BSD) - Riza Gusti Rahayu (MUKASI: Jurnal Ilmu Komunikasi, 2024)
Student motivation is the key to the success of an educational process, with fluctuations in motivation, whether increasing or decreasing, often being an internal factor of the student. However, teachers play a crucial role in supporting and enhancing student motivation. In efforts to increase student motivation, teachers employ persuasive communication to alter the understanding of students experiencing challenges in learning motivation. This study examines the persuasive communication strategies used by teachers at SD Islam Sinar Cendekia BSD to enhance student learning motivation. Using a descriptive qualitative approach and a case study method, data were collected through observations and interviews with teachers. The findings of the study indicate that before implementing persuasive communication, teachers are guided to understand the students' character so that the persuasive message aligns with the students' emotional conditions, which undoubtedly facilitates the teachers in providing examples or analogies to support the persuasive message. Additionally, teachers also align student character with the design and implementation of learning, the outcomes of which reflect the teachers' credibility in applying persuasive communication strategies